Analisis Pengaruh Retrofit Refrigeran R407c Ke R450a Mesin Pendingin Hvac Pada Instalasi Lepas Pantai - Subagio, Slamet (Jurnal Sosial Teknologi, 2025)
This study aims to analyze the refrigerant retrofit process from R407C to R450A in HVAC systems installed on offshore facilities. R450A was selected as an alternative due to its lower Global Warming Potential (GWP) and thermodynamic properties comparable to R407C. The methodology includes empirical data collection of system performance, comparative analysis of operational parameters, and technical evaluation of necessary component modifications. The results indicate that the use of R450A can improve energy efficiency by up to 5-10% and significantly reduce greenhouse gas emissions. Furthermore, the retrofit can be implemented without major modifications to the main system components, making it technically and economically feasible. Technical challenges encountered during the retrofit process were identified, and recommendations were provided to mitigate implementation risks. This study contributes to the development of more environmentally friendly and energy-efficient cooling systems in the offshore industrial sector.